Perception of a divergent family of phytocytokines by the Arabidopsis receptor kinase MIK2 - Jack Rhodes (Nature Portfolio, 2021)
Secreted peptides and cell-surface localized receptor kinases allow plants to modify growth and development according to external cues. Here, Rhodes et al. show that the MIK2 receptor perceives the SERINE RICH ENDOGENOUS PEPTIDE (SCOOP) family of phytocytokines and is capable of recognising Fusarium-derived SCOOP-like peptides.